What if… we could virtually restore and visit a pre-war church to the highest fidelity possible with no 3D scanning available? - Scharffhausen, Jean-Baptiste; Teixeira, João Marcelo X. N. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
The digital study of the historical and sacred parts of the church of Thillois aimed to enhance understanding and preservation of this significant heritage site, severely impacted by the First World War. By employing digital tools and technologies, this study facilitated the creation of a comprehensive 3D model of the church, incorporating detailed analyses of historical archives and the restored building. This effort not only reconstructed the physical attributes of the church but also addressed the sociocultural impact of the war on the local community. Key stages of the study included detailed computational modeling, photogrammetry, and the integration of VR to provide an immersive experience for users. The study highlighted the challenges and limitations of digital restoration, such as the passive nature of video animations and the physical distance between the observer and the digital model. Nevertheless, the VR experience allowed users to interact with the model, enhancing accessibility and engagement with the heritage site. The research underscored the importance of consistent and regular documentation to support future studies and enhance collective memory. Digital methods and tools complemented traditional documentation, offering new ways to access, reformulate, and understand historical information. The studys findings have significant implications for similar heritage sites in the Reims region and beyond, demonstrating the social and cultural potentials of digital tech- nologies, fanning the flames of collective memory as a source of social and civic cohesion, and virtually and more intensely restoring architectural spaces lost or altered by historical events.